University of Florida Potato Variety Trials Spotlight: Marcy - Mario H. M. L. Andrade; Rodrick Z. Mwatuwa; Christian T. Christensen; Lincoln Zotarelli (EDIS, 2021)
‘Marcy’ is a white-flesh and white-skinned fresh-market potato variety released from the Cornell University Potato Breeding program in 1990. The cultivar was selected from a cross between ‘Atlantic’ and Q155-3 (De Jong et al. 2006). In trials conducted at the University of Florida, ‘Marcy’ demonstrated high yield and good tuber characteristics compared to its matched commercial standards, ‘Atlantic’ and ‘La Chipper’. After its release, ‘Marcy’ has been cultivated in several trials in Florida. Production and quality results provided here are from variety trials conducted by the University of Florida Hastings Agricultural and Extension Center in 2002 and from 2011 to 2019.